Skills development and international development agenda setting: lessons from an intervention in northern Nigeria - Bano, M (Palgrave Macmillan, 2017)
Skills development remains on the international development agenda but fails to get adequate attention. Based on prolonged fieldwork with a particularly marginalised community of children and young adults in the northern Nigerian state of Kano, this article shows how in contexts of extreme poverty the demand for skills training can supersede that for basic education. Further, by drawing on results of a six-month-long skills-training intervention, the article documents the scope for increased experimentation in the delivery of low-cost community-based skills-training programmes and identifies factors that influence programme completion. It also demonstrates that participation in skills-training programmes can dramatically increase entrepreneurial aspirations among marginalised youth; but that without access to credit most fail to pursue their aspirations. Below certain poverty thresholds, the dire resource constraints make change in aspirations an unreliable predictor of possible improvement in future outcomes.